Breaking bad news: Effects of forecasting diagnosis and framing prognosis. Issue 1 (January 2016) - Porensky, Emily K.; Carpenter, Brian D.
Highlights: We used video vignettes to evaluate two communication strategies in cancer. Warning was not associated with lower psychological distress or better recall. Positive framing led to less distress and more hope than negative framing. Positive framing also diminished recall of some prognosis statistics. This is a step toward evidence-based approaches for communicating bad news. Abstract: Objective: Research to support guidelines for breaking bad news is lacking. This study used an experimental paradigm to test two communication strategies, forecasting bad news and framing prognosis, in the context of cancer. Methods: In a 2 × 2 design, 128 participants received bad news in a hypothetical consultation. A videotaped physician presented diagnostic and prognostic information, varying warning (warning shot vs. no warning), and framing (positive vs. negative). Effects on psychological distress, recall accuracy, and subjective interpretations of the news were assessed. Results: Warning was not associated with lower psychological distress or improved recall. Individuals who heard a positively-framed prognosis had significantly less psychological distress, rated their prognosis better, and were more hopeful than those who heard a negatively-framed prognosis. However, they also showed a trend toward reduced accuracy in recalling prognostic statistics. Conclusions: Results contribute to a growing body of literature exploring optimal approaches for communicating bad news in health care. Practice Implications: Although research in clinical settings is needed to bolster results, findings suggest that when providers use positive framing to reduce distress about prognosis, they should also consider ways to overcome potential reductions in recall accuracy, such as repeating statistical information or supplementing with written information.